Digital Agreements On The Legal Validity Of Electronic Signatures In Online Lending From The Perspective Of Indonesian Legislation - Septi Fitria Ningsih; Hurairah Hurairah; Widya Timur (JURNAL HUKUM SEHASEN, 2026)
The rapid development of information technology has led to the increasing use of digital agreements in various sectors, including online lending services (fintech lending). In practice, digital agreements commonly use electronic signatures as a form of consent between the parties. However, there are still debates regarding the legal validity and evidentiary strength of electronic signatures under Indonesian positive law, particularly in relation to the provisions of the Indonesian Civil Code and the Law on Information and Electronic Transactions (ITE Law). This study aims to analyze the validity of electronic signatures in digital online lending agreements and to examine the legal certainty of their evidentiary value based on Indonesian legislation. This research employs normative legal research methods with statutory and conceptual approaches through literature review of primary, secondary, and tertiary legal materials. The results show that electronic signatures are legally valid as long as they comply with the requirements stipulated in the ITE Law and its implementing regulations and do not contradict the legal requirements of contracts under Article 1320 of the Indonesian Civil Code. Furthermore, electronic signatures possess lawful evidentiary value in civil procedural law as electronic evidence. However, their effectiveness largely depends on the legality of electronic system providers, the use of certified electronic signatures, and the quality of security systems applied. Therefore, stronger harmonization between the Civil Code and the ITE Law is necessary to ensure legal certainty in digital agreements, particularly in online lending services, in order to achieve optimal legal protection for the parties involved.